Assessing the impact of information and communication management on institutional performance : proceedings - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
The report covers the workshop themes and conclusions, and lists the main principles of impact assessment.